Assessment of the effectiveness and efficiency of the West Africa medicines regulatory harmonization initiative by the member countries - Owusu-Asante, Mercy; Darko, Delese Mimi; Walker, Stuart; Salek, Sam (Frontiers in Pharmacology, 2022)
Background: The West Africa Health Organization launched the West Africa Medicines Regulatory Harmonization Project (WA-MRH) in 2017 with the overarching objective to improve the availability of high-quality, safe and effective medicines and vaccines by the 15 countries in the Economic Community of West African States region. Although this project has made significant progress towards the realisation of its goals, challenges still remain. The aims of this study were to evaluate the effectiveness and efficiency of the WA-MRH, examine what challenges are being encountered and identify strategies that would strengthen the process for realising the initiative’s goals. Methods: The Process Effectiveness and Efficiency Rating (PEER) questionnaire was used to collect data from assessors representing the seven active NMRAs in the joint assessment procedure that identified the benefits, challenges and recommendations for improving the performance of the WA-MRH project. Results: The benefits of the joint assessment procedure include time savings to manufacturers resulting from submitting one dossier and the same response package to multiple countries resulting in access to the multiple African markets within the same timeframe. Additionally, some of the NMRAs have been able to strengthen their technical capacity as a result of this initiative. Key challenges to the project include the lack of a robust information technology system that would enable dossier tracking and constraints in human resources needed to support dossier submissions and the assessment process. Conclusion: This study identified the strengths of the WA-MRH initiative as well as strategies for improvement and achievement of its objectives. The centralised submission of a dossier and its tracking is key to the regulatory assessment process. This research has demonstrated that amongst other considerations, a robust information technology system, coupled with the necessary human resource capacity would greatly enhance the effectiveness and efficiency of the WA-MRH initiative.